Mechanisms in the bed nucleus of the stria terminalis involved in control of autonomic and neuroendocrine functions: A review - Crestani, Carlos Cesar [UNESP]; Alves, Fernando H. F.; Gomes, Felipe V.; Resstel, Leonardo B. M.; Correa, Fernando M. A.; Herman, James P. (Bentham Science Publishers, 2013)
The bed nucleus of the stria terminalis (BNST) is a heterogeneous and complex limbic forebrain structure, which plays an important role in controlling autonomic, neuroendocrine and behavioral responses. The BNST is thought to serve as a key relay connecting limbic forebrain structures to hypothalamic and brainstem regions associated with autonomic and neuroendocrine functions. Its control of physiological and behavioral activity is mediated by local action of numerous neurotransmitters. In the present review we discuss the role of the BNST in control of both autonomic and neuroendocrine function. A description of BNST control of cardiovascular and hypothalamus-pituitary-adrenal axisactivity at rest and during physiological challenges (stress and physical exercise) is presented. Moreover, evidence for modulation of hypothalamic magnocellular neurons activity is also discussed. We attempt to focus on the discussion of BNST neurochemical mechanisms. Therefore, the source and targets of neurochemical inputs to BNST subregions and their role in control of autonomic and neuroendocrine function is discussed in details. © 2013 Bentham Science Publishers.
Keywords: BNST; Cardiovascular function; Extended amygdala; HPA axis; Neurotransmitters; Stress and physical exercise; Vasopressin; 2 (2 methoxy 1, 4 benzodioxan 2 yl) 2 imidazoline; 2 (2 methoxy 1,4 benzodioxan 2 yl) 2 imidazoline; 2 [[2 (2, 6 dimethoxyphenoxy) ethyl] aminomethyl] 1, 4 benzodioxan; 2 [[2 (2,6 dimethoxyphenoxy)ethyl]aminomethyl] 1,4 benzodioxan; 4 aminobutyric acid; 5 [2 [[2 hydroxy 3 [4 (1 methyl 4 trifluoromethyl 2 imidazolyl) phenoxy] propyl] amino] ethoxy] salicylamide; 5 [2 [[2 hydroxy 3 [4 (1 methyl 4 trifluoromethyl 2 imidazolyl)phenoxy]propyl]amino]ethoxy]salicylamide; acetylcholine; bicuculline methiodide; cannabidiol; carbachol; cobalt chloride; corticotropin releasing factor; decahydro 6 phosphonomethyl 3 isoquinolinecarboxylic acid; glutamic acid; muscimol; neurotransmitter; nitric oxide; noradrenalin; oxytocin; unclassified drug; vasopressin; arterial pressure; autonomic nervous system; behavior; blood pressure; brain stem; chemoreceptor reflex; dynamic exercise; electrostimulation; exercise; fear; forebrain; human; hypothalamus; immobilization stress; magnocellular nucleus; microdialysis; nerve conduction; neuroendocrine system; neurotransmission; nonhuman; physiological process; pressoreceptor; review; stria terminalis